Determination of the Wall Thickness of Block Copolymer Vesicles by Fluorescence Lifetime Imaging Microscopy. Issue 4 (20th December 2016) - Handschuh‐Wang, Stephan; Wesner, Daniel; Wang, Tao; Lu, Pengyu; Tücking, Katrin‐Stephanie; Haas, Simon; Druzhinin, Sergey I.; Jiang, Xin; Schönherr, Holger
Abstract : This study reports on the characterization of reporter dye‐loaded block copolymer vesicles (polymersomes) of PS115 ‐ b ‐PAA15 (polystyrene‐block‐poly(acrylic acid)) and PEG114 ‐ b ‐PLA167 (poly(ethylene glycol)‐block‐poly(lactic acid)) and their drying behavior by fluorescence lifetime imaging microscopy (FLIM). The characteristic changes of the fluorescence decay components of the dye calcein incorporated in the three different local nanoenvironments, namely, the solvated dye, dye associated with the vesicle wall, and dried agglomerated dye, are observed by FLIM during the drying of vesicles. The amplitude ratio R 1/2 of the components attributed to the solvated dye in the vesicle interior with a lifetime τ1 ≈ 3.9 ns to the one attributed to calcein associated with the wall with a lifetime τ2 ≈ 1.5 ns is found to decrease exponentially with drying time. The time constants, which are found to depend linearly on the radius of the vesicle, yield by extrapolation to zero vesicle diameter an estimate of the polymersome wall thickness. For PS115 ‐ b ‐PAA15 and PEG114 ‐ b ‐PLA167 vesicle wall thicknesses r 0 of 16 ± 5 nm and 28 ± 4 nm, respectively, are observed, which are in favorable agreement with transmission electron and atomic force microscopy data. Abstract : Fluorescence lifetime imaging microscopy reveals the drying kinetics of polymeric vesicles. The analysis of the excited state lifetimes of the reporter dye calcein in the different nanoenvironments of polymersomes affords time‐resolved information about the water content of nanocapsules and from the vesicle size dependence an estimate for the wall thickness.